Assessment of indoor environmental comfort for individuals wearing face masks of different thickness - Łukasz Jan Orman; Luiza Dębska; Lidia Dąbek; Stanislav Honus; Stanisław Adamczak (Archives of Environmental Protection)
The present paper experimentally analyses the subjective assessment of indoor environment comfort based on a questionnaire survey conducted in a climate chamber located at Kielce University of Technology (Poland), if two types of face masks are worn by the respondents: thin (medical) and thick (cotton-made) masks. Air temperature and relative humidity in the chamber ranged from around 19 to 28oC and 20 – 70%, respectively. Precise measurement of the microclimate parameters was obtained with a microclimate meter, which recorded air temperature and relative humidity at the moment of completing the questionnaires. The respondents were of similar age (22 – 31 years old) and wore two types of clothing during the experiments: summer and winter, which differed by thermal resistance. This value amounted to 0.5 clo for the summer outfit and 0.8 clo for the winter one.In total 960 questionnaires were analysed in the study. The results indicate that the increase in air temperature led to poorer overall comfort, while the largest comfort sensation was recorded for the most favourable thermal sensation range. In general, thicker masks provided lower overall comfort than thinner masks for all relative humidity values.